The SSC-DTI Business Education on Accounting and Training for SMEs (SSC-DTI-BEATS) Program: Its Implementation and Sustainability - Bongalonta, Michael B.; Bongalonta, Michelle M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed the implementation and sustainability of the SSC-DTI Business Education on Accounting and Training for SMEs (SSC-DTI-BEATS) Program of Sorsogon State University, conducted from 2018 to 2023. Specifically, it evaluated program implementation, examined sustainability in terms of number of beneficiaries, economic, social, and technical aspects, and identified factors contributing to its sustainability. The study also explored changes brought by the program to the lives of its beneficiaries. A mixed-methods design was employed. Quantitative data were used to measure sustainability levels, while qualitative insights were gathered through Focus Group Discussions (FGDs) with beneficiaries. The FGDs provided thematic validation of results, particularly on the role of collaborative partnerships, resource adequacy, and monitoring practices. Findings show that the SSC-DTI BEATS Program was fully implemented during the Memorandum of Agreement period and achieved very high sustainability across all dimensions. Beneficiaries reported improved business knowledge and practices, leading to enhanced financial management and better quality of life. The study concludes that strong institutional collaboration, active stakeholder engagement, and efficient resource management are critical in sustaining extension programs. It recommends replicating the program’s second phase, “GROW NEGOSYO,” using the same strategies to ensure continuity and maximize benefits.